Glutamine supplementation enhances development of in vitro-produced porcine embryos and increases leucine consumption from the medium. Issue 5 (31st May 2018) - Chen, Paula R; Redel, Bethany K; Spate, Lee D; Ji, Tieming; Salazar, Shirley Rojas; Prather, Randall S
Abstract: Improper composition of culture medium contributes to reduced viability of in vitro-produced embryos. Glutamine (Gln) is a crucial amino acid for preimplantation embryos as it supports proliferation and is involved in many different biosynthetic pathways. Previous transcriptional profiling revealed several upregulated genes related to Gln transport and metabolism in in vitro-produced porcine blastocysts compared to in vivo-produced counterparts, indicating a potential deficiency in the culture medium. Therefore, the objective of this study was to determine the effects of Gln supplementation on in vitro-produced porcine embryo development, gene expression, and metabolism. Cleaved embryos were selected and cultured in MU2 medium supplemented with 1 mM Gln (control), 3.75 mM Gln (+Gln), 3.75 mM GlutaMAX (+Max), or 3.75 mM alanine (+Ala) until day 6. Embryos cultured with +Gln or +Max had increased development to the blastocyst stage and total number of nuclei compared to the control ( P  < 0.05). Moreover, expression of misregulated transcripts involved in glutamine and glutamate transport and metabolism was corrected when embryos were cultured with +Gln or +Max. Metabolomics analysis revealed increased production of glutamine and glutamate into the medium by embryos cultured with +Max and increased consumption of leucine by embryos cultured with +Gln or +Max. As an indicator of cellular health, mitochondrial membrane potential was increased when embryos were cultured with +Max which was coincident with decreased apoptosis in these blastocysts. Lastly, two embryo transfers by using embryos cultured with +Max resulted in viable piglets, confirming that this treatment is consistent with in vivo developmental competence. Abstract : Supplemental glutamine in porcine embryo culture medium modulates gene expression and enhances metabolic activity of in vitro-produced blastocysts.